A Study of The Relationship Among Shopee E-commerce Platform E-service Quality, E-trust, E-customer Satisfaction and Behavioral Intentions of Online Shopping Customers - Galih Pratama; Erlita Ridanasti (International Journal of Management Science and Information Technology, 2023)
This research makes a significant contribution by exploring the relationship between service quality, electronic trust, electronic customer satisfaction, and the purchasing behavior intention of online female customers. Employing a quantitative approach with purposive sampling, data was collected from 259 respondents in Yogyakarta and its surrounding areas through Google Form questionnaires. The data analysis, conducted using t-tests and simple linear regression in SPSS, revealed that electronic service quality has a positive and significant impact on electronic trust and electronic customer satisfaction. Electronic trust also shows a significant positive effect on electronic customer satisfaction. Electronic customer satisfaction, electronic trust, and electronic service quality each have a positive and significant influence on behavioral intention. These findings hold strategic implications for e-commerce companies in improving responsiveness to consumer issues, aiming to enhance overall service quality, build customer trust, create electronic customer satisfaction, and encourage positive behavioral intentions in online shopping.